Systematic Approach for Alignment of Light Field Mirage - Yoshiharu Momonoi; Koya Yamamoto; Yoshihiro Yokote; Atsushi Sato; Yasuhiro Takaki (Applied Sciences, 2022)
We previously proposed techniques to eliminate repeated three-dimensional (3D) images produced by the light field Mirage, which consists of circularly aligned multiple-slanted light field displays. However, we only constructed the lower half of the system to verify the proposed elimination techniques. In this study, we developed an alignment technique for a complete 360-degree display system. The alignment techniques for conventional 360-degree display systems, which use a large number of projectors, greatly depend on electronic calibration, which indispensably causes image quality degradation. We propose a systematic approach for the alignment for the light field Mirage, which causes less image quality degradation by taking advantage of the small number of display devices required for the light field Mirage. The calibration technique for light field displays, the image stitching technique, and the brightness matching technique are consecutively performed, and the generation of 360-degree 3D images is verified.